Pengaruh Media Wayang Profesi untuk Meningkatkan Keterampilan Menyimak Cerita Pendek - Jumyati Jumyati; Ujang Jamaludin (Departement of Mathematics Education, 2022)
Listening is a human activity more than just speaking, reading, and writing. Teachers must be creative in making learning media so that students understand the meaning of communication that occurs when learning takes place. based on observations made during class IV SD Negeri Pasir Gadung it can be seen that the teacher only uses reading text. The existence of media as a real object in learning really helps the process of delivering material. one of the media that is suitable for use, especially in listening to stories, is the Profession Puppet media. The advantages of this media mean that the presentation of short story material becomes more innovative, professional wayang media is also easy to use and can be taken anywhere. This type of research means pre-experimental with a single class pretest-posttest. The subjects in this study were all fourths grade students at Pasir Gadung State Elementary School for the 2022/2023 academic year, a total of 25 students. Data collection techniques in this study were tests and documentation. It can be seen from the results obtained in this study that 70 is the origin of the pre-test mean value and 82 is the origin of the post-test mean value using professional wayang media. This is a sign that learning using professional wayang influences the skills of listening to stories of fourth graders of Pasir Gadung State Elementary School.